Notes on the nesting biology of five species of Euglossini (Hymenoptera: Apidae) in the Brazilian Amazon - Carvalho-Filho, Fernando da Silva; de Oliveira, Favizía Freitas (EntomoBrasilis, 2017)
Abstract. The orchid bees (Euglossini) are medium to large-sized species with fully or partially metallic body that are relatively common in the Neotropical Region. Nevertheless, the nesting biology of many species remains unknown. Therefore, the objective of this paper is to provide new information on the nesting biology of five species of Euglossini found in urban and forested sites of Brazilian Amazon. The nests of Eufriesea pulchra (Smith)and Euglossa chalybeata Friesewere recorded for the first time, found in an active nest of the ant Azteca sp. and in a fallen rotting tree, respectively. The nest of Euglossa townsendi(Linnaeus) was found in the leaf of an ornamental plant Cordyline sp. (Asparagaceae), also newly recorded. Euglossa intersecta Latreillewas recorded nesting in an abandoned termite nest, and Euglossa cordataCockerell was found nesting in a tubular metal window handle. Notas sobre a biologia de nidificação de cinco espécies de Euglossini (Hymenoptera: Apidae) na Amazônia Brasileira Resumo. As abelhas-da-orquídea (Euglossini) possuem tamanho médio a grande, corpo parcialmente ou completamente metálico e são relativamente comuns na região Neotropical. Apesar disso, a biologia de nidificação da maioria das espécies permanece desconhecida. Portanto, o objetivo deste estudo e fornecer novas informações sobre a biologia de nidificação de cinco espécies de Euglossini encontradas em área urbana e florestada da Amazônia Brasileira. Os ninhos de Eufriesea pulchra (Smith)e Euglossa chalybeata Frieseforam registrados pela primeira vez, encontrados dentro de ninho de formiga Azteca sp. e em uma árvore apodrecida caída, respectivamente. O ninho de Euglossa townsendiCockerell foi registrado pela primeira vez em uma folha da planta ornamental Cordyline sp. (Asparagaceae). Euglossa intersecta Latreillefoi registrada nidificando dentro de um ninho abandonado de cupim e Euglossa cordata (Linnaeus)foi encontrada nidificando em uma maçaneta tubular de metal de uma janela.